Effects of living arrangements on youth perceptions of grandparenting roles - Imran Abdul Haqiim Aman Shah (2015)
With a rapidly ageing population in Singapore, more and more families are choosing to live apart from their elderly. Most studies have focused on the parent and grandparent perspectives to account for why the living arrangements are changing – but what effect do these changes have on the youth? Should we be concerned about the effect of youth having diminished contact with their grandparents? A sample of 18 respondents interviewed: six who co-resided with their grandparents, six who lived apart from their grandparents, and another six who stayed with their grandparents in different phases of their lives. Respondents were selected based on their total contact hours spent and willingness to be interviewed. Those who spent more contact hours with their grandparents by living with them preferred to identify positively with the values and narratives of their grandparents than respondents who lived separately. Respondents who lived separately were also more likely than both the co-residing respondents, and the respondents who co-resided in different phases, to regard their grandparent’s values with ambivalence. Common to all respondents in all groups were their perspectives of their families’ ideas and practices of filial piety. Most youth were optimistic about being able to enjoy privacy and personal space living apart, without compromising the quality of their relationships with their elders.